Novel artificial tricalcium phosphate and magnesium composite graft facilitates angiogenesis in bone healing - Yuan-Hsin Tsai; Chun-Chieh Tseng; Yun-Chan Lin; Howida M. Nail; Kuan-Yu Chiu; Yen-Hao Chang; Ming-Wei Chang; Feng-Huei Lin; Hui-Min David Wang (Biomedical Journal)
Background: Critical bone defects pose a significant challenge for orthopedic surgeons. Autologous bone grafting is the golden standard. However, it is hindered by issues such as donor site morbidity and limited availability. Commercially available artificial bone grafts may encounter challenges in properly integrating the surrounding bone tissue, potentially leading to delayed or incomplete healing. Furthermore, magnesium deficiency has been shown to negatively affect localized angiogenesis and bone repair. As a result, creating a synthetic biomaterial that includes magnesium could serve as an excellent bone substitute. The study aims to evaluate and test the morphological, mechanical, and biological properties of a calcium phosphate cement (CPC) sponge composed of tetracalcium phosphate (TTCP) and monocalcium phosphate monohydrate (MCPM). Methods: This study aims to develop biomedical materials composed mainly of TTCP and MCPM powder, magnesium powder, and collagen. The materials were prepared using a wet-stirred mill and freeze-dryer methods. The particle size, composition, and microstructure of the materials were investigated. Finally, the biological properties of these materials, including 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay for biocompatibility, effects on bone cell differentiation by alkaline phosphatase (ALP) activity assay and tartrate-resistant acid phosphatase (TRAP) activity assay, and endothelial cell tube formation assay for angiogenesis, were evaluated as well. Results: The data showed that the sub-micron CPC powder, composed of TTCP/MCPM in a 3.5:1 ratio, had a setting time shorter than 15 min and a compressive strength of 4.39 ± 0.96 MPa. This reveals that the sub-micron CPC powder had an adequate setting time and mechanical strength. We found that the sub-micron CPC sponge containing magnesium had better biocompatibility, including increased proliferation and osteogenic induction effects without cytotoxicity. The CPC sponge containing magnesium also promoted angiogenesis. Conclusion: In summary, we introduced a novel CPC sponge, which had a similar property to human bone promoted the biological functions of bone cells, and could serve as a promising material used in bone regeneration for critical bone defects.